Computational fluid dynamics analysis on thermal performance of solar air heater with inclined fins - Qader, Bootan Sherzad (2018)
The depletion of fossil fuel reserves and rise in price instability of fossil fuels and also the impacts of global warming have accelerated the development of renewable energy sources as a reliable alternative energy source. The solar energy is a clean, sustainable, abundant and renewable energy source that has attracted the interest of various researchers across the world for solar energy with related applications. Similarly, solar irradiance can be absorbed by the solar collectors from the sun and thereafter, it is converted to convenient heat needed for heating air. The design of solar air heater is simple and commonly used in different areas of application. The thermal performance of the conventional solar air heater is found to be poor due to low convective heat transfer coefficient between heat collecting surface and working fluid. The main objective of this research is to increase the convection heat transfer coefficient in order to increase the performance of thermal system. In this study, a numerical evaluation was carried out on the heat transfer and the flow friction processes in a solar air heater coupled with inclined fins located underneath the absorber plate. With the constant heat flux application, the average Nusselt number and friction factor as well as the thermo-hydraulic performance parameter (THPP) were comprehensively investigated. The research covered various length of fin in the range of 1.5-2.5 mm, different slant angle (α) of fin in the range of 30°-60°, different pitch (P) of fin in the range of 15-25 mm, and a range of 4,000-24,000 for the Reynolds numbers. For the current computational fluid dynamic (CFD) evaluation, (ANSYS FLUENT v16.1) with renormalization group ƙ − ε turbulence model is selected for analysis computational domain. In general, a significant improvement of the heat transfer in a solar air heater having inclined fins has been achieved. The maximum value of 174.05 was observed for the average Nusselt number which corresponds to a length of fin e=2.5mm, slant angle α=60 ̊ and pitch P=15mm at a Reynolds number of (24,000) for the of parameter range investigated. While, the maximum friction factor of 0.046 was observed which corresponds to a length of fin e=2.5mm, slant angle α=60 ̊ and pitch P=15mm at a Reynolds number of (4,000). Moreover, the quadratic model created by the response surface methodology (RSM) for computation of the THPP was found so that it is applied to a high degree of accuracy to quantify the operating performance of the solar air heater. Based on results of the model, the optimized values of design parameters for the optimal operation of solar air heater to provide the optimal THPP of 1.928 were found to be; length of fin = 1.52 mm, the pitch of fin = 19.04 mm, slant angle = 49° and Reynolds number of 18243.5. According to the optimized values of design parameters, the enhancement ratio of Nusselt number, friction factor and the THPP were found to be 2.53, 2.22 and 1.928, respectively. These correspond to the improvement of the Nusselt number by 153%, the friction factor by 122% as well as the THPP by 92.8% compared to the smooth duct. Finally, the thermal performance of the proposed inclined fin in terms of THPP was compared to other roughness geometries, such as circle (THPP=1.65), square-sectioned (THPP=1.80) and L-shaped (THPP=1.90). Accordingly, a better THPP of 1.928 was observed for the current study.